Optimization of Dynamic Behaviour of Tram (Current Problems in Rail Vehicles, 2021)
At ŠKODA TRANSPORTATION there is paid a considerable attention to optimizing dynamic behaviour of new trams during their designing and developing. The first phase of designing new trams is performed using numerical simulations on MBS models in the Adams VI-Rail software, which are able to predict the dynamic behaviour of trams with high accuracy. individual structural nodes of trams are optimized according to the results of performed calculations in order to achieve the best dynamic behaviour of trams. In the second phase, measurements and tests are performed on a real tram, which refine results of calculations performed on MBS models and also serve for MBS model validation. This approach makes it possible to predict and optimize the dynamic behaviour of trams with minimal costs and, if necessary, to make design changes in the designing phase. This paper deals with an influence of upper intersection connection on the dynamic behaviour of tram when passing in curve and the optimization of the intersection connection.
Keywords: tram; dynamic behaviour; curve; intersection connection